FILOSOFI IDEOLOGIS MOHAMMAD HATTA: JALAN TENGAH ANTARA LIBERALISME DAN SOSIALISME-KOMUNISME DALAM KONTEKS INDONESIA - Detri; M.Nursi; Hendrizal; Dilla Desfrita Wahyuni; Rika Novita (STKIP Subang, 2026)
Mohammad Hatta's ideological thinking is one of the important foundations in formulating the direction of ideology and development of the Indonesian nation. Hatta did not position himself as an extreme ideology of liberalism or socialism-communism, but rather formulated a middle path rooted in the values ​​of the people, social justice, and human morality. This article aims to analyze Mohammad Hatta's ideological philosophy and examine the fundamental differences between his thinking and the ideologies of liberalism and socialism-communism in the Indonesian context. This research uses a qualitative approach with a library research method on Bung Hatta's works and relevant contemporary scientific articles from the past five years. The results of the study show that Hatta criticized liberalism for its tendency to give rise to social inequality due to the dominance of individualism and free market mechanisms, while socialism-communism was criticized for denying individual freedom and potentially giving rise to state totalitarianism. As an alternative, Hatta offered the concept of people's democracy and a cooperative economy that balances individual and collective interests. Hatta's ideological philosophy positions the state as a regulator that ensures social justice, not as an absolute ruler or facilitator of a free market. Thus, Bung Hatta's thinking represents a uniquely Indonesian ideology that is relevant as a reference in addressing the challenges of social inequality and sustainable development in the contemporary era.